2022
DOI: 10.1101/2022.11.17.516919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All-or-None Evaluation of Prediction Certainty in Autism

Abstract: The brain generates predictions to prepare for upcoming events. As life is not always 100% predictable, it also estimates a level of certainty for these predictions. Given that autistic individuals resist even small changes in everyday life, we hypothesized impaired tuning of prediction certainty in autism. To study this, EEG was recorded from adolescents and young adults with autism while they performed a probabilistic prediction task in which cue validity was parametrically manipulated. A fully predictable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Reduced phase concentration and inter-trial phase coherence to the cues in the autistic group suggested that impaired neural entrainment contributed to reduced temporal precision in the CNV. In a separate EEG study on adults with ASD (ages: 16-28 years old), we found that the CNV was less modulated by how likely the target was to occur (Reisli et al, 2022), and notably here too the CNV appeared to be less temporally locked to the onset of the target (e.g., more distributed across the cue-target interval; see Figure 2). Collectively these CNV and phase coherence data suggest less precision in the alignment of neural activity with temporally predictable events.…”
Section: Predictive Processing and The Role Of Synchronizationmentioning
confidence: 80%
See 1 more Smart Citation
“…Reduced phase concentration and inter-trial phase coherence to the cues in the autistic group suggested that impaired neural entrainment contributed to reduced temporal precision in the CNV. In a separate EEG study on adults with ASD (ages: 16-28 years old), we found that the CNV was less modulated by how likely the target was to occur (Reisli et al, 2022), and notably here too the CNV appeared to be less temporally locked to the onset of the target (e.g., more distributed across the cue-target interval; see Figure 2). Collectively these CNV and phase coherence data suggest less precision in the alignment of neural activity with temporally predictable events.…”
Section: Predictive Processing and The Role Of Synchronizationmentioning
confidence: 80%
“…FIGURE 2Examples of altered modulation of predictive processing in ASD, using two different prediction paradigms: (A) timing (prediction of "when"); and (B) content (prediction of "what." In both paradigms, EEG of the ASD groups showed reduced modulation by the manipulations than controls [modified fromBeker et al (2021) andReisli et al (2022)]. …”
mentioning
confidence: 99%